2017
DOI: 10.1016/j.jcot.2016.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Current trends of microorganisms and their sensitivity pattern in paediatric septic arthritis: A prospective study from tertiary care level hospital

Abstract: is still the most common organism in septic arthritis. The BACTEC system was found to improve the yield of clinically significant isolates. Though a significant resistance to common antibiotic regimen is noticed, the strain is susceptible to cephalosporin group of antibiotics. We recommend the use of cephalosporine antibiotics as an empirical therapy till culture and sensitivity report are available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 10 publications
(12 reference statements)
0
6
0
Order By: Relevance
“…A multicentre review of 45 neonates found positive joint fluid cultures in 85% of the patients [ 4 ]. The BACTEC method commonly used for blood cultures is superior to the conventional agar plate method for synovial fluid samples as well [ 12 ]. The diagnosis was made by an initial assessment of the vitals, physical examination, and blood tests.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A multicentre review of 45 neonates found positive joint fluid cultures in 85% of the patients [ 4 ]. The BACTEC method commonly used for blood cultures is superior to the conventional agar plate method for synovial fluid samples as well [ 12 ]. The diagnosis was made by an initial assessment of the vitals, physical examination, and blood tests.…”
Section: Discussionmentioning
confidence: 99%
“…However the choice of antibiotic therapy is by local protocol. There is no clear consensus on the duration of antimicrobial treatment or mode of delivery for this condition [ 12 ]. The concentration of the antibiotic in the synovial fluid equals the serum concentration one hour after infusion, making intravenous infusion a very effective delivery mechanism for acute infection [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…[36][37][38]40 Second, the rising incidence of multidrug-resistant infections is increasingly documented globally as an emerging threat in both equine [61][62][63][64][65][66][67][68][69][70][71] and human clinical practice, with orthopaedic and joint surgery being affected similarly to other specialties. [72][73][74][75][76] These trends prompt re-evaluation of antibiotic protocols in general, including local injection or use in intra-synovial lavage, as inappropriate dosing may further induce greater development of resistance with potentially significant detrimental ramifications for both horses and staff in equine veterinary hospitals. 71 Multidrug-resistant bacterial isolates have been shown to be more frequently cultured from horses previously undergoing procedures or hospitalisation and those treated with antibiotics, although this trend has not been investigated specifically in relation to antibiotic use in joints.…”
Section: Ris K S and Con S Ider Ati On S With Intr A-arti Cul Ar Antib I Oti C Injec Tionsmentioning
confidence: 99%
“…are most commonly associated with septic arthritis in humans. [73][74][75] In equine patients, Enterobacteriaceae spp. are more commonly cultured from joint infections resulting from penetrating wounds while Staphylococcus spp.…”
Section: Ris K S and Con S Ider Ati On S With Intr A-arti Cul Ar Antib I Oti C Injec Tionsmentioning
confidence: 99%
See 1 more Smart Citation